Active Learning through Project Based Learning Approach in English Language Lessons for Early Age Groups - Tabassum Murtaza, Mahvesh Mahmood (JECCE, 2023)
The purpose of this research is to determine how Project Based Learning (PBL) approach influenced students’ cognitive and emotional engagement in Class I English lessons. Project-based learning is a dynamic classroom approach in which students actively explore real-world problems and challenges and acquire a deeper knowledge. This research attempted to see how the use of self-assessment, students writing daily reflection logs, parental involvement, interviewing a security personnel and engaging students in exploring a real-world problem like safety at public places, influenced their engagement and interest in English language classroom. Furthermore, cross-curricular/interdisciplinary and Information Communication Technology (ICT) integration kept the students intrinsically motivated. Questionnaires were designed for School Heads and Class I English teachers. The study was conducted in fifty schools with 180 sections and a strength of 3893 students. The results showed that as the driving question was relevant to the prevailing security situation in our country, the level of student engagement was immense throughout the project Unit. However, due to less interest taken by the parent body, some students could not get real life experiences. The findings showed that planning, teaching, management and assessment of PBL is relatively challenging for teachers.